2011
DOI: 10.1038/ejcn.2011.163
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reproducibility of a web-based, self-administered food frequency questionnaire

Abstract: Background/Objectives: To assess the validity and the reproducibility of a newly developed web-based, self-administered food frequency questionnaire (web-FFQ). Subjects/Methods: A total of 74 healthy subjects (34 men and 40 women) from the Québec City metropolitan area were asked to complete, in random order, the web-FFQ, a validated interviewer-administered FFQ (IA-FFQ) and a 3-day food record (3-day FR). Results: Mean intakes of 17/22 nutrients assessed between the web-FFQ and the 3-day FR were not significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
137
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(163 citation statements)
references
References 29 publications
23
137
3
Order By: Relevance
“…Correlations observed between these two assessment tools were within the ranges noted by other investigators, from 0?27 to 0?71 for vitamin C (33)(34)(35)(36)(37) , from 0?33 to 0?75 for vitamin E (38)(39)(40) and from 0?14 to 0?38 for total carotenoids and respective subclasses (41,42) . Additionally, since the correlation analysis for testing validity has been questioned for its failure in measuring agreement (30,43) , Bland-Altman plots and cross-classification were used in the present study to bridge this gap (44) . Bland-Altman plots did not show any systematic bias.…”
Section: Discussionmentioning
confidence: 99%
“…Correlations observed between these two assessment tools were within the ranges noted by other investigators, from 0?27 to 0?71 for vitamin C (33)(34)(35)(36)(37) , from 0?33 to 0?75 for vitamin E (38)(39)(40) and from 0?14 to 0?38 for total carotenoids and respective subclasses (41,42) . Additionally, since the correlation analysis for testing validity has been questioned for its failure in measuring agreement (30,43) , Bland-Altman plots and cross-classification were used in the present study to bridge this gap (44) . Bland-Altman plots did not show any systematic bias.…”
Section: Discussionmentioning
confidence: 99%
“…Correlation coefficients for carotenoid subclasses were generally higher than those from preceding FFQ (44,45) . Additionally, since the correlation analysis for testing validity has been questioned for its failure in measuring agreement (3,46) , cross-classification was used in the present study to bridge this gap (47) . Cross-classification for the current FFQ indicated reasonable agreement across tertiles of antioxidant intake between the 30 d FR and FFQ and an acceptable low misclassification percentage, which further suggested that our FFQ could provide a similar ranking of antioxidant intake as did the 30 d FR.…”
Section: Discussionmentioning
confidence: 99%
“…Online dietary assessment tools have used similar approaches to standard methods and include FFQ (17)(18)(19) , 24 h recalls (20)(21)(22) and dietary records (1,23) . Some tools are a hybrid method such as the Oxford WebQ, which is presented as a 24 h recall but relies on reporting of twenty-one food groups (24) over a 24 h period.…”
Section: Development Of Web-based Tools To Measure Dietmentioning
confidence: 99%